2006
DOI: 10.1177/0883911506071967
|View full text |Cite
|
Sign up to set email alerts
|

Folate-Modified Cholesterol-Bearing Pullulan, a New Cancer-Targeted Nanoparticle Drug Carrier: Synthesis and Applications

Abstract: Folate-modified cholesterol-bearing pullulan (FA-CHP) was synthesized by the reaction of folic acid [.beta]-2-aminoethylamide and 4-nitrophenyl chloroformate-activated cholesterol-bearing pullulan. The substitution ratio was estimated as 10% per glucoside units. Several combinations of FA-CHP, unmodified cholesterol-bearing pullulan (CHP) and doxorubicin (DOX) mixtures were tested for cancer-selective cytotoxicity in vitro. A combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The FA-CHP used in this study was prepared as reported previously [15], with slight modifications. The chemical structure of FA-CHP is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The FA-CHP used in this study was prepared as reported previously [15], with slight modifications. The chemical structure of FA-CHP is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…FA-CHP used in this study was prepared as reported previously [15] with slight modifications. Briefly, CHP (8 g) was activated by 4-nitrophenyl chloroformate (PNPC), before conjugating with folic acid ␥-2-aminorthylamide (EDA-FA).…”
Section: Synthesis Of Fa-chpmentioning
confidence: 99%
See 1 more Smart Citation
“…Pullulan targets the liver and has anticancer activity (Hosseinkhani et al, 2002;Sunamoto et al, 2006). SAP nanoparticles were tested without ATRA on hepatocellular carcinoma HepG2 cells using the MTT assay.…”
Section: In Vitro Drug Release and Cytotoxicity On Cancer Cellsmentioning
confidence: 99%
“…Many investigations have reported that some amphiphilic pullulan derivatives can form self-aggregated NPs to be used as the carrier for drug delivery (Zhang et al, 2009;Yang et al, 2010;Lee et al, 2012;Yang et al, 2014). Cholesterol-modified pullulan (CHP), as one of amphiphilic pullulan derivatives, can be synthesized using 1,6-hexyldiisocyanate linkages by the reaction between cholesterol and pullulan (Akiyoshi et al, 1993), and its selfaggregated CHP NPs can be used as drug delivery systems (Akiyoshi et al, 1998;Ikuta et al, 2002;Sunamoto et al, 2006;Shimoda et al, 2012) or artificial molecular chaperones (Nomura et al, 2003;Asayama et al, 2008). The outstanding characteristics of cholesterol-modified pullulan attract our group to engage in this research.…”
Section: Introductionmentioning
confidence: 99%